2018
DOI: 10.4251/wjgo.v10.i10.344
|View full text |Cite
|
Sign up to set email alerts
|

miR-122-5p as a novel biomarker for alpha-fetoprotein-producing gastric cancer

Abstract: AIMTo investigate the clinical utility of alpha-fetoprotein (AFP)-producing gastric cancer (AFPGC)-specific microRNA (miRNA) for monitoring and prognostic prediction of patients.METHODSWe performed a comprehensive miRNA array-based approach to compare miRNA expression levels between AFP-positive and AFP-negative cells in three patients with primary AFPGC. We next examined the expression levels of the selected miRNAs in five AFPGC and ten non-AFPGC tissue samples by quantitative reverse transcription-polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…In addition, miR-122 promotes aggression and epithelial-mesenchymal transition in TNBC [ 57 ] and cell survival in radio-resistance cells [ 58 ]. High plasma miR-122 levels have been detected in AFP-producing gastric cancer [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-122 promotes aggression and epithelial-mesenchymal transition in TNBC [ 57 ] and cell survival in radio-resistance cells [ 58 ]. High plasma miR-122 levels have been detected in AFP-producing gastric cancer [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although α-fetoprotein-producing gastric cancer (AFPGC) has been recognized as an aggressive gastric cancer (11,12), to the best of our knowledge no comprehensive molecular analysis has been reported for this uncommon subtype. We previously identified that miR-122-5p was significantly highly expressed in AFPGC tissues and could be a useful plasma biomarker in patients (9). Moreover, we revealed that miR-122-5p exhibited a strong correlation with malignant potential in clinical settings (9).…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, we hypothesized that some specific miRNAs may play crucial roles in AFPGC. Previously, we demonstrated that miR-122-5p was significantly higher in AFPGC tissues and that the plasma expression level may be a useful biomarker in patients with AFPGC (9). In the present study, we examined the biological function of miR-122-5p and the molecular mechanism underlying tumor progression in AFPGC.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the association between miR-100-3p and ERK/AKT and Bax-Bcl2-Cas-pase3 pathways was investigated, and the results showed that over-expression of miR-100-3p inhibited the ERK/ AKT pathway and activated the Bax-Bcl2-Caspase3 pathway, whereas knockdown of miR-100-3p activated the ERK/AKT pathway and inhibited the Bax-Bcl2-Caspase3 pathway, likely via BMPR2. miRNA dysregulation has been reported to be valuable for GC diagnosis [30][31][32]. Recently, several studies even demonstrated the potential of miRNA in GC diagnosis and treatment [33,34].…”
Section: Discussionmentioning
confidence: 99%